OVERVIEW OF THE COMPONENT ENHANCEMENT METHODS IN DEVELOPMENT OF THE GAS CONDENSATE FIELDS - A. V. Volokhova; E. V. Zemlyanaya; V. V. Kachalov; V. N. Sokotuschenko (Наука. Инновации. Технологии)
In this review of researches of domestic and foreign authors the problem of increase of a component of gas condensate layers is considered. Introduction. The reasons for the reduction of component recovery in gas condensate fields and solutions to this problem are discussed. Improving the performance of existing wells based on the phenomenon of decompression beginning of condensation of the condensate with increasing of the composition of hydrocarbons «pentane + higher». Methods for pumping water or inert gas along the ield circuit to maintain reservoir pressure at the supercritical level are also considered, but they have not been distributed. Materials and methods. The rational operation methods are based on the idea of maintaining reservoir pressure above the condensation pressure. In contrast to oil production, in the operation of gas condensate fields are used, as a rule, modes of development of productive formation «at depletion». On an industrial scale, the only method used to maintain reservoir pressure at the supercritical level is the Cycling process, i.e. injection of dry methane into the reservoir [1]. Results and discussions. The use of a particular field development scheme with an impact on the reservoir should allow for the additional extraction of some of the residual gas and condensate reserves. In oil fields, well washing with various solutions is widely used. For gas-condensate fields, except for solvents, which eliminates mudding of nearield is proposed the injection of reagents that produce heat during the reaction. Due to the increase in temperature, the phase equilibrium of the gas condensate mixture is shifted towards the gas phase, which should lead to an increase in the yield of gas condensate. The article discusses some of the results of the work devoted to solving the issues of the most complete extraction of gas from productive formations. Summary. All promising physico-chemical methods of influence on the formation in order to increase condensate recovery can be classified as follows: 1. Rational operation of a single well or field as a whole. 2. Injection of gas or liquid into the reservoir. 3. Use of solvents. 4. Impact explosion, acoustic and elastic waves, electromagnetic impact. 5. Thermal effect. The study showed that different operating scenarios can adjust the composition of the extracted products and the amount of condensate in the reservoir.